The impact of skill endowments and collective bargaining on knowledge-intensive greenfield FDI - Sara Amoroso; Mafini Dosso; Pietro Moncada-Paternò-Castello (European Commission, Joint Research Centre (JRC), 2015)
This paper assesses the contribution of skilled employment and labour market conditions to the ability of attracting knowledge intensive and manufacturing greenfield FDI. We carry out our analysis by controlling for a wide range of labour market features, such as the collective bargaining coverage rate, the non-wage labour costs, and the occupational skills of employment. It departs from the existing literature in two respects. First, it deepens the analysis on the effect of labour market regulations and skills endowments on greenfield FDI inflows. Second, it investigates the extent to which labour market characteristics matter for discriminating among `resource-seeking' and `efficiency/strategic asset-seeking' greenfield FDI activities (e.g. manufacturing versus knowledge-intensive foreign investments, respectively). Our empirical analysis suggests that the quality of employment and the technological knowledge base have different impact on the location of knowledge-intensive and on low-cost labour-intensive manufacturing foreign investments. Further, associating the collective bargaining coverage of unions with the level of regulation in the labour market, our results can provide insights into the effectiveness of labour market policies that aim at attracting knowledge-intensive investments. Length: 25 pages
Keywords: O32; F16; J51; 330; foreign direct investment; unions R&D